Effect of McKenzie’s Approach on Functional Mobility in Bilateral Knee Osteoarthritis - T Kadam, Sonali; B Shinde, Sandeep (International Journal of Psychosocial Rehabilitation, 2020)
BACKGROUND— Osteoarthritis (OA) is a degenerative disorder of the joint causing pain, varying degrees of functional limitation, and reduced quality of life. There are various treatment strategies used to treat OA and found to be effective, but McKenzie is one such approach, which is based on directional preference of pain and has been applied to the spine and found to be effective in reducing symptoms but not on the knee. so the present study was done to find the effect of McKenzie's approach on functional mobility in subjects with bilateral knee osteoarthritisOBJECTIVES—1) To study the effect of McKenzie’s approach on pain and functional mobility in bilateral knee osteoarthritis.2) To study the effect of conventional physiotherapy on pain and functional mobility in bilateral knee osteoarthritis3) To compare the effect of McKenzie’s approach and conventional physiotherapy on pain and functional mobility in bilateral knee osteoarthritis.MATERIAL AND METHODS: 64 subjects diagnosed as OA were selected as subjects. Subjects were divided into 2s, 32 in each group. Group A received the McKenzie group of exercises, while group B received the conventional group of exercises. pre- and post-assessment of pain. Disability and functional mobility were taken by visual analogue scale (VAS), WOMAC, stand-up-and-go test , step length, and stride length, respectively.RESULT: McKenzie’s approach have extremely significant result in reducing pain and disability and improving functional mobility and walking endurance, with post interventional score 2.56+0.84 for VAS, 34.1+8.67 for WOMAC, and 8.89+1.10 for STAND UP AND GO TEST, respectively and has considerable significant improvement in gait parameters, with post interventional score 64.06+8.17 for step length and 8.89+1.10, respectively, compared than conventional exercisesCONCLUSION: McKenzie exercises have asignificant effect on functional mobility in subjects with bilateral knee osteoarthritis, as with gait parameters.